PERAN DIGITAL MARKETING DI ERA DIGITALISASI DALAM MENDORONG PERTUMBUHAN UMKM DI KABUPATEN BANTAENG - Annisah Nurul Fadilah T; Marini Sumarni; Miftahul Nurjannah Jamal (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the role of digital marketing in driving the growth of Micro, Small, and Medium Enterprises (MSMEs) in Bantaeng Regency, with a focus on digital marketing strategies and their impact on product visibility and sales. Using a qualitative approach through in-depth interviews and observations of two MSMEs: Laura Clothing Store and Indah Learning Tutoring, the results show that digital marketing through TikTok, Instagram, WhatsApp, and Shopee is effective in expanding market reach, increasing brand awareness, and product sales. The strategies implemented include SEO, content marketing, social media marketing, and paid advertising. However, MSMEs face challenges such as budget constraints, difficulty managing content, and a lack of technical knowledge. The study concludes that digital marketing has great potential to support MSME growth, but requires adaptive strategies and training and guidance to overcome these obstacles.